Obesity and Sleep in The Covi̇d-19 Proces (Turkey Health Literacy Journal, 2022)
The Covid-19 pandemic is the first global pandemic whose effects have reached deadly levels in terms of health. The long-term of the process has led people to change their daily habits and lead them to continue their lives in a limited environment. The aim of this study is to explain in detail how obesity and sleep, which are directly related to each other, have changed in the Covid 19 process and how much of an effect they have on our daily life and health. For scanning, the keywords "pandemic, covid-19, obesity, sleep, nutrition during the pandemic" were searched in the "Google Scholar, Pubmed and Endnote" search. The findings obtained after the screening revealed that the stress, boredom, fear and risk of death caused by Covid 19 increased the anxiety levels of individuals. These increased negative situations caused sleep disorders, daytime well-being and psychological states worsened, and it was stated that, unlike normal processes, more fat, carbohydrate and protein consumption was observed. The fact that individuals have increased the amount of food consumption and inactivity levels has increased the susceptibility to obesity, and a long-term and dangerous vicious circle has emerged. For this reason, since the relationship between sleep and obesity are factors that directly affect each other, the negative situation experienced in one of them during the Covid 19 process negatively affected the other.It has been observed that the formation of unhealthy eating habits increases the risk of heart disease, diabetes and obesity in general.Controlled diet, regular sleep and exercise can be recommended to prevent this negative relationship.